KONSEP DIRI DAN SELF DISCLOSURE REMAJA BROKEN HOME - Iswatun Khasanah; Kartini Rosmalah Dewi Katili (Makna: Jurnal Kajian Komunikasi, Bahasa, dan Budaya, 2021)
In the condition of broken home family especially for a teenager there are many concepts that are classified negatively with their own causative factors one of them is having a family that is not harmonious. During this transition from childhood to adulthood that the concept began to form. Self- concept is our own beliefs and self-perception. and a teenager's ability to communicate interpersonally also affects self-opening. The purpose of this research is to find out the picture of self- concept and self disclosure of broken home adolescents. The method used was qualitatively descriptive with in-depth interviews of six broken home teens with different foster patterns. The results showed that teenagers from broken home families had positive and negative self-concepts. Positive self-concepts have traits: feeling disliked by others, feeling hopeless and doing negative things. Negative self-concepts have traits: tend to feel disliked by others, experience barriers to interacting with their social environment, feel hopeless/negative, and unable to control themselves in the midst of conflict. While in self disclosure broken home teenagers tend to have an open and closed attitude. Characteristics of self disclosure open attitude include: assessing messages objectively and being able to distinguish easily and see nuances. While the characteristics of a closed attitude include: assessing messages based on personal motives, more on the source of the message than the content of the message, and teaching information about other people's beliefs from the source itself. For further research can explore the social influence on the formation of broken home adolescent self concept using the theory of social communication psychology.